2018
DOI: 10.1088/2399-6528/aacccb
|View full text |Cite
|
Sign up to set email alerts
|

Negation of photon loss provided by negative weak value

Abstract: We propose a usage of a weak value for a quantum processing between preselection and postselection. While the weak value of a projector of 1 provides a process with certainty like the probability of 1, the weak value of −1 negates the process completely. Their mutually opposite effect is approved without a conventional 'weak' condition. In addition the quantum process is not limited to be unitary; in particular we consider a loss of photons and experimentally demonstrate the negation of the photon loss by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Although such a symmetric relation of the positive weak value 1 and the negative one −1 was also confirmed as linearpolarization shift in [47], I have shown that the symmetric relation is also found in the post-selection probability without another system of polarization. Actually the supplementary result of Figure .5(b) in [46] implies such a symmetric relation when T is large (i.e. R << 1).…”
Section: A Weak Value Appearing As a Back-action Via A Post-selectionmentioning
confidence: 84%
See 3 more Smart Citations
“…Although such a symmetric relation of the positive weak value 1 and the negative one −1 was also confirmed as linearpolarization shift in [47], I have shown that the symmetric relation is also found in the post-selection probability without another system of polarization. Actually the supplementary result of Figure .5(b) in [46] implies such a symmetric relation when T is large (i.e. R << 1).…”
Section: A Weak Value Appearing As a Back-action Via A Post-selectionmentioning
confidence: 84%
“…In this discussion of [46], the negative weak value of −1 by itself does not make sense, since the negative value cannot be related to 'negation' without the positive value. In other words the negative weak value of −1 is meaningful in the equation, 1 − 1 = 0.…”
Section: A Weak Value Appearing As a Back-action Via A Post-selectionmentioning
confidence: 97%
See 2 more Smart Citations
“…It also has been a beneficial measurement tool in application [30]- [37]. Moreover weak value itself has been found to be useful for description of a quantum phenomenon [38]- [44].…”
Section: πSamementioning
confidence: 99%